A reference neutron field for measurement of spectrum averaged cross sections. (1st June 2020) - Košťál, Michal; Schulc, Martin; Losa, Evžen; Šimon, Jan; Burianová, Nicola; Novák, Evžen; Mareček, Martin; Uhlíř, Jan; Czakoj, Tomáš; Rypar, Vojtěch; Juříček, Vlastimil; Capote, Roberto; et al.
Highlights: Setting of reference neutron field in LR-0 reactor. Calculation and measurement of selected reactions reaction rates in LR-0. Discrepancies between calculation and experiment. Measurement of (n, 2n) reaction spectral averaged cross sections of 75 As; 90 Zr; 23 Na; 89 Y; 55 Mn; 127 I; 19 F; 197 Au. Measurement of spectral averaged cross sections of lower threshold 27 Al(n, α); 24 Mg(n, p); 48 Ti(n, p) reactions. Abstract: A new reactor neutron reference field is proposed, which can be used for measurements of spectrum averaged cross sections (SACS). The reference field is identified in the center of a dry irradiation channel surrounded by six 3.3% enriched fuel assemblies assembled in the zero-power LR-0 reactor with negligible burn-up. The neutron field can be defined as a reference one, because of the well-defined neutron spectrum and neutron flux, well-characterized criticality and core power distribution, and reproducibility of results. Extensive experimental validation was undertaken. A new reference field can be used for the measurement of reaction rates and SACS used in nuclear data validation. It is shown that above 6 MeV the spectrum is undistinguishable from the thermal-neutron induced 235 U prompt fission neutron spectrum (PFNS). Thus, when a reaction has threshold over this limit, the SACS in the thermal-neutron induced 235 U fission neutron field can be derived from reaction rates obtained in this reference neutron field. A comprehensive set of SACS measurements with uncertainties below 5% in the reference field is presented.